Historical process of creation of the Santo Antônio Settlement in Porto Nacional-TO: a historical reading through rural education - George Leonardo Seabra Coelho; Greyg Lake Oliveira Costa (Universidade Federal do Norte do Tocantins, 2022)
In this work we will approach the historical process of regularization of the Santo Antônio Settlement - located in the municipality of Porto Nacional-TO - and the creation of the Municipal Education Center of Campo Chico Mendes. In order to do so, we will make a brief exposition on the performance of the National Institute of Colonization and Agrarian Reform (INCRA) in the national land reorganization, the settlement policies in the Fernando Henrique Cardoso Government and in the Government of Luiz Inácio Lula da Silva. We will also expose the issue of citizenship and the main social movements that have established links with Agrarian reform. Finally, we will present the historical process of creation of the Santo Antônio settlement, the physical structure and the Political Project of the Chico Mendes School. We consider that it is extremely important to understand how the creation of this settlement took place because, in addition to being one of the oldest settlements in the municipality of Tocantins, this study may offer subsidies so that teachers can use this study to discuss the History of the Settlement.